Developing Coffeeshop Improvement Strategy by Considering Voice of Customer - Abhiseka Pandya; Dyah Ismoyowati; Suharno Suharno (Agroindustrial Journal, 2021)
The improvement strategy of coffee shop was created by first analyzing the quality of product, service, and pricing of coffee shop to determine the customer requirements using questionnaire. 105 customers of Legend Coffee filled the questionnaire. From 30 attributes, 13 of them needed improvement as their performance rating were below their respective importance, thus resulted in low customer satisfaction. Some product quality and service attributes located in the Concentrate Here quadrant, which requires immediate improvement. Based on those results, then strategic improvements will be made with management using QFD. The highest prioritized improvement strategies are increase in human resources with training in accordance with the job description, increase supervision of each division, and clearer preparation and more detailed SOPs. Improvement strategies then developed based on the voice of the customer with a discussion with management.